Long‐term effect of the self‐management comprehensive coping strategy program on quality of life in patients with breast cancer treated with high‐dose chemotherapy. Issue 3 (31st January 2012) - Gaston‐Johansson, Fannie; Fall‐Dickson, Jane M.; Nanda, Joy P.; Sarenmalm, Elisabeth Kenne; Browall, Maria; Goldstein, Nancy
Abstract Background This study aims to examine the effectiveness of a self‐management multimodal comprehensive coping strategy program (CCSP) on quality of life (QOL) among breast cancer patients 1 year after treatment. Methods Patients (n = 110) with stage II, III, or IV breast cancer scheduled to receive high dose chemotherapy and autologous hematopoietic stem cell transplantation were randomized to either CCSP treatment or control group. The CCSP intervention was taught 2 week before hospital admission with reinforcement at specified times during treatment and 3 months after discharge. The CCSP components included educational information, cognitive restructuring, coping skills enhancement, and relaxation with guided imagery. Instruments administered at baseline included the following: Quality of Life Index—Cancer Version (QOLI‐CV), State–Trait Anxiety Inventory, Beck Depression Inventory, and Coping Strategies Questionnaire. At 1‐year follow‐up, patients (n = 73) completed and returned the follow‐up QOLI‐CV. Results Patients were mainly ≥40 years of age, married, Caucasian, and diagnosed with advanced breast cancer. A model measuring effectiveness of CCSP on QOL (total and subscale) at 1‐year follow‐up showed that the CCSP group (n = 38) had significant improvement in overall QOL (p < 0.01), health and functioning (p < 0.05), and socioeconomic (p < 0.05) and psychological/spiritual well‐being (p < 0.01) compared with the control group (n = 35). The CCSP patients frequently used the CCSP to manage psychological (51%) and sleep problems (60%). Conclusions The CCSP improved QOL for patients at 1‐year follow‐up. Patients overwhelmingly reported that CCSP was beneficial. The CCSP as an effective coping intervention has potential as a self‐management program for breast cancer survivors. Copyright © 2012 John Wiley & Sons, Ltd.